PROJECT BASED LEARNING SEBAGAI MODEL PEMBELAJARAN TEKS ANEKDOT PADA SISWA SMA - Hanifah, Farah; Putriani; Zulfikar, Moh. Fikri (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research aims to analyze and present the learning model of Project Learning (PjBL) in the context of education, with a focus of Discourse covering education definitions, factors affecting educational performance, the quality of human resources, the role of teachers in the teaching process, and the implementation of PjBL in improving education quality. The research uses descriptive qualitative methods with data collection techniques through library study. The results of this study show that PjBL has proven to be effective in improving student skills, connecting learning with real life, and providing opportunities for teachers and students to collaborate. However, there are weaknesses, such as the required time and large funds. Applying PjBL can help improve problem-solving skills and creativity.